Pengayaan kandungan antioksidan daging ayam melalui marinasi dengan jus buah andaliman (Zanthoxylum acanthopodium) - Kurniawan Sinaga; Nur (Journal of Pharmaceutical and Sciences, 2023)
Andaliman fruits are known for high antioxidants and antibacterial ingredients. This herb has a high potential to pretend oxidation and contamination of foodstuffs, such as meat. The research aims to investigate the effect of marination with andaliman fruit juice on chicken meat antioxidant activity and Salmonella availability. About 12 samples of duck meat were divided into 4 groups such as 0 % andaliman fruit juice (P0), andaliman fruit juice 10 % (P1), andaliman fruit juice 15 % (P2), and andaliman fruit juice 20 % (P3). Each group consisted of 3 samples. Antioxidant activity and Salmonella availability were examined in the research. The research showed that Antioxidant activity P0 was about 18,33 %, P1 (23,46 %), P2 (9,01 %), and P3 (13,35 %). Salmonella examination showed that P0 positive, P1 positive, P2 positive, and P3 negative. E. coli test showed that all treatments were negative. The research concluded that marination with 10 % andaliman fruit juice increases the antioxidant activity of chicken meat and marination with 20 % could erase Salmonella availability in chicken meat.